Inherited Diseases of Platelet Glycoproteins: Considerations for Rapid Molecular Characterization - Bray, Paul F (Thrombosis and Haemostasis, 1994)
The characterization of inherited diseases of platelets has provided valuable information about platelet physiology and platelet protein function. Genetic studies on patients with Glanzmann thrombasthenia, the Bemard-Soulier syndrome, and platelet-type von Willebrand disease have been confined to abnormalities of the GPIIb-IIIa and GPIb-IX receptor complexes. The primary molecular technique used in these analyses has been the polymerase chain reaction (PCR). The amplified PCR products are either directly sequenced, or used to screen for abnormal regions of the genes which are then sequenced. This review examines the known mutations in GPIIb-IIIa and GPIb-IX, focusing on those genetic issues which should dictate decisions regarding the approach to identifying molecular defects. The techniques for characterizing mutant alleles in Glanzmann thrombasthenia and Bernard-Soulier syndrome are described and a general strategy is offered. Because mutations resulting in reduced levels of transcripts can be missed when screening RNA, an argument is made for using genomic DNA as the primary material for mutation detection.